3D mapping of the Wolf–Rayet nebula M 1-67: clues for post-common envelope evolution in massive stars. Issue 3 (26th April 2022) - Zavala, S; Toalá, J A; Santamaría, E; Ramos-Larios, G; Sabin, L; Quino-Mendoza, J A; Rubio, G; Guerrero, M A
ABSTRACT: We present a 3D mapping of the Wolf–Rayet (WR) nebula M 1-67 around WR 124. We obtained high-resolution San Pedro Mártir (SPM) Manchester Echelle Spectrograph (MES) observations along 17 long-slit positions covering all morphological features in M 1-67. We are able to unveil the true morphology of M 1-67 and its kinematics by interpreting the SPM MES observations by means of the 3D modelling tool for Astrophysics shape . Our shape model that best reproduces the SPM MES data includes three concentric bipolar structures composed by a hollow ellipsoidal structure and a torus. In addition, the model requires the presence of expanding jets and broken blisters in order to reproduce specific spectral features. Our results are consistent with the idea that M 1-67 and its progenitor star WR 124 have formed through a common envelope scenario that occurred 11.8$^{+4.6}_{-0.8}$  kyr ago. Our bipolar model strongly questions previous suggestions of the presence of a bow shock structure surrounding M 1-67. We interpret that the bright structures detected in the spectra extracted from the central regions are produced by wind compression at the receding region of the innermost structure in M 1-67. Furthermore, WR 124 is moving through a low-density region above the Galactic plane that has negligibly affected the formation history of M 1-67.